In-depth Analysis of the Effects of Smart Services on Value Creation - Reinhold, Jannik; Frank, Maximilian; Koldewey, Christian; Dumitrescu, Roman; Buss, Eugen (Proceedings of the ISPIM Connects Bangkok – Partnering for an Innovative Community)

Value-centered design of a digital service robotics platform - Menzefricke, Jörn Steffen; Frank, Maximilian; Drewel, Marvin; Dumitrescu, Roman (Procedia CIRP)

Identification of socio-technical changes caused by Industry 4.0 - Schnasse, Felix; Menzefricke, Jörn Steffen; Gabriel, Stefan; Hobscheidt, Daniela; Parlings, Matthias; Kühn, Arno; Dumitrescu, Roman (Proceedings of the Hamburg International Conference of Logistics (HICL))

Aligning Strategy and Structure for Smart Service Businesses in Manufacturing - Koldewey, Christian; Gausemeier, Jürgen; Chohan, Nadia; Frank, Maximilian; Reinhold, Jannik; Dumitrescu, Roman (Proceedings of the IEEE International Conference on Technology Management, Operations and Decisions ”Disruptive Technologies and Social Impacts”)

Systematische Entwicklung von Normstrategien für Smart Services - Koldewey, Christian; Frank, Maximilian; Gausemeier, Jürgen; Bäsecke, Alexander; Reinhold, Jannik; Dumitrescu, Roman (ZWF Zeitschrift für wirtschaftliche Fabrikplanung)
Die Verfügbarkeit von Daten aus dem Betrieb hat durch die Einführung von vernetzten intelligenten Fertigungssystemen (cyber-physische Systeme) stark zugenommen. Hieraus eröffnen sich Erfolg versprechende Möglichkeiten für Smart Services und damit verbundene neue Geschäftsfelder. Voraussetzung für den Eintritt in ein neues Geschäft mit Smart Services ist eine fundierte Geschäftsstrategie. Wir zeigen die zentralen Gestaltungsfelder von Smart Service-Strategien auf und erläutern, wie sechs von uns ermittelte Normstrategien bei der Formulierung einer attraktiven Strategie helfen können.
Keywords: Smart Service; Digitalisierung; Industrie 4.0

Planning a Smart Service Business Integrating External Partners - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Managing Digital Open Innovation)
Today’s manufacturing industry is confronted with fundamental changes in value creation. The tension between the two megatrends of digitization and servitization leads to new hybrid market offerings, so-called smart services. Corresponding business models and value networks fundamentally differ from traditional ones. Developing smart services requires an advanced management of business models and new competences in young disciplines, while their provision requires new internal and external organizational structures or processes. To strengthen their competitive position, manufacturing companies need to extend their business model portfolios and adapt their value networks. However, the highly complex transformation of value creation especially challenges small and medium-sized companies due to limited competences and resources. They must consider opening their boundaries and collaborating with partners. In this chapter, we introduce a basic framework for designing smart services and present a methodology for the planning of a smart service business integrating external partners. The methodology is structured into five phases: Examination of smart service portfolio, analysis of business models and environment, business model portfolio planning, competence identification and analysis, and value creation planning. The methodology is explained by an example on cable marker printers.
Keywords: Smart Service; Digitalisierung; Industrie 4.0

Method for data inventory and classification - Massmann, Melina; Meyer, Maurice; Frank, Maximilian; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Data-Driven Product Generation and Retrofit Planning - Meyer, Maurice; Frank, Maximilian; Massmann, Melina; Wendt, Niklas; Dumitrescu, Roman (Procedia CIRP)

Datengetriebene Steigerung der Verfügbarkeit - Uhlmann, Eckart; Dumitrescu, Roman; Polte, Julian; Meyer, Maurice; Simsek, Deniz (wt Werkstattstechnik online)

Framework for Data Analytics in Data-Driven Product Planning - Massmann, Melina; Meyer, Maurice; Frank, Maximilian; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Procedia Manufacturing)

GEMINI-Modellierungssprache für Wertschöpfungssysteme - Reinhold, Jannik; Koldewey, Christian; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

GEMINI-Geschäftsmodellmuster-Kartenset - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Geschäftsmodellvalidierung - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Geschäftsmodell-Roadmapping - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Framework and Functionality Patterns for Smart Service Innovation - Koldewey, Christian; Meyer, Maurice; Stockbrügger, Patrick; Dumitrescu, Roman; Gausemeier, Jürgen (Procedia CIRP)

The impact of the 4th industrial revolution on the design fields of innovation management - Niewöhner, Nadine; Asmar, Laban; Röltgen, Daniel; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Der Industrie 4.0 Maturity Index in der betrieblichen Anwendung. Aktuelle Herausforderungen, Fallbeispiele und Entwicklungstrends (acatech KOOPERATION) - Schuh, Günther; Anderl, Reiner; Dumitrescu, Roman; Krüger, Antonio; ten Hompel, Michael

Significance and Challenges of Data-driven Product Generation and Retrofit Planning - Massmann, Melina; Meyer, Maurice; Dumitrescu, Roman; Enzberg, Sebastian von; Frank, Maximilian; Koldewey, Christian; Kühn, Arno; Reinhold, Jannik (Procedia CIRP)

Gestaltung hybrider Wertschöpfung und Arbeit im Kontext von Smart Services - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman; Frank, Maximilian; Schweppe, Thomans; Melzer, Annegret (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb)

Strategie als Erfolgsfaktor - Koldewey, Christian; Dumitrescu, Roman (ServiceToday)